Proyecto de Factibilidad para la creación de una Empresa Avícola dedicada a la producción y comercialización de Huevos Orgánicos a base de omega 3 y 6 en la Ciudad de Loja - Jumbo Loaiza, María Del Cisne (2018)
In the present we live in a society in continuous industrial, technological, social, mental change, that every time advances at a faster speed, every time we are more demanding and every time we are more nonconformist. Therefore, the market seeks to satisfy the needs of the consumer and be able to be better than the competition. This is where the food industry wants to continue researching and innovating to meet the needs of the consumer. In the present in which we live, health is one of the main concerns of society and that is where the healthy diet intervenes, even so, we do not want to leave aside the pleasure of a varied diet. In this work, I present the acceptance and adaptation in the market of a food innovation, a functional food that improves the unhealthy part of the eggs and combines it with the healthy part, to get an adequate product for society. raises the "PROJECT OF FEASIBILITY FOR THE CREATION OF A POULTRY COMPANY DEDICATED TO THE PRODUCTION AND COMMERCIALIZATION OF ORGANIC EGGS BASED ON OMEGA 3 AND 6 IN THE CITY OF LOJA." The objective of this project was to determine the "feasibility of implementing a company that produces and markets eggs enriched with omega 3 and 6 in the city of Loja" For a reliable working methods such as inductive and deductive were used and the observation techniques, survey was applied to families of urban city parishes, giving a total of 381 surveys and interviews were used to the owners of different businesses and companies that sell eggs enriched with omega 3 and 6 existing in the city of Loja. Within the discussion the different studies that make up the project were developed, where in the market study it was determined that the target market is made up of the families of the parishes of the city of Loja. Also based on the results of the surveys it was possible to carry out the analysis of the potential, real, effective and unsatisfied 5 demand, in addition to knowing the tastes and preferences of the potential customers that will be covered with the product. Through the technical study, the necessary resources are considered so that the company can develop its production activities, such as machinery and equipment, productive capacity, project engineering, physical distribution, and it was possible to identify the optimal macro and micro location of the project concluding that the city of Loja and specifically in the sector the Tenería is the ideal place for the execution of the project. It will be legally constituted as a Unipersonal Limited Liability Company. As for the financial study, the project requires an initial investment of $ 19.158,29 dollars, fixed assets with a total of $ 9.438,30 dollars; deferred assets $ 900.00 dollars and a working capital of $ 8.819,99. The financing will be 48% of own capital and 52% financed by Banco del Austro. The total cost for the first year is $ 49.430,34 and $ 59.461,00 income is the breakeven 74.33%, depending on the installed capacity, based on sales of $ 44.198,37 is dollars and depending on the production, 10.400,00 buckets. The project will achieve profits for the first year is $ 6.903,02; In the same way, the flows for the five years of useful life were calculated, being for the first year of $ 9.733,84 and for the other years they are all positive. The financial evaluation with its respective financial indicators are: Net Present Value (NPV) is $ 82.540,35; Internal Rate of Return (IRR) of 65,37%; Cost Benefit Ratio (RBC) is $ 37 cents for every dollar invested; Period of Capital Recovery (PRC) is 1 years, 11 months and 19 days; and finally, the Sensibility Analysis shows that the project supports an increase in costs of 21,70% and a decrease in Revenues of 15,90%. The project has all the necessary guarantees to ensure its viability and projected profitability. Finally, the conclusions and recommendations reached were determined, based on the results obtained.